Do unemployment benefits and employment protection influence suicide mortality? An international panel data analysis - Horst Rottmann (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2014)
We examine the economic and social determinants of suicide mortality in a panel of 25 OECD countries over the period 1970 - 2011 and explicitly analyze the effects of unemployment and labor market institutions on suicide rates. In line with a large body of literature, our results suggest that unemployment and social factors are important determinants of suicide mortality. The results also indicate that unemployment benefits decrease suicides of males, while relatively strict employment protection regulations increase suicide mortality. These findings indicate that labor market institutions may influence job satisfaction and the quality of life in industrial countries. We suggest taking into account the role of labor market institutions when analyzing the effects of institutional and economic determinants on health.
Keywords: C23; E24; I10; J65; 330; Panel Data; Suicide; Employment Protection; Unemployment Benefits